Sagot :
Answer:
[tex]1. \: y = \: {4}^{3} - 4(4) ^{2} + 2(4) - 6 \\ y = 64 - 4(16) + 8 - 6 \\ y = 64 - 64 + 2 \\ y= 0 + 2 \\ P(x) = 2[/tex]
[tex]2. \: y = 2^{5} - 3 ({2})^{2} - 20 \\ y = 32 - 3(4) - 20 \\ y = 32 - 12 - 20 \\ y = 32 - 32 \\ p(x) = 0[/tex]
[tex]y = 2({9})^{3} + 3( {9})^{2} - 9 - 79 \\ y = 2(729) + 3(81) - 88 \\ y = 1458 + 243 - 88 \\ y = 1701 - 88 \\ p(x) = 1613[/tex]
-JDCD
Step-by-step explanation:
Auto substitute the x values to x variables. P(x) and Y are one(identical),so don't be confused.
-JDCD